Handbook of Sociological Theory
XIII, 745 p.
Keywords: Sociology is experiencing what can only be described as hyperdifferentiation of theories - there are now many approaches competing for attention in the intellectual arena . From this perspective, we should see a weeding out of theories to a small number, but this is not likely to occur because each of the many theoretical perspectives has a resource base of adherents. As a result, theories in sociology do not compete head on with each other as much as they coexist. This seminal reference work was brought together with an eye to capturing the diversity of theoretical activity in sociology - specifically the forefront of theory. Contributors describe what they themselves are doing right now rather than what others have done in the past. The goal of this volume is to allow prominent theorists working in a variety of traditions - who wouldn't usually come together - to review their work. The chapters in this volume represent a mix of theoretical orientations and strategies, butthese these theories are diverse and represent the prominent theoretical discussions in sociology today. Some areas included are: Section I: Theoretical Methodologies and Strategies Section II: The Cultural Turn in Sociological Theorizing Section III: Theorizing Interaction Processes Section IV: Theorizing from the Systemic and Macrolevel Section V: New Directions in Evolutionary Theorizing Section VI: Theorizing on Power, Conflict, and Change SectionVII: Theorizing from Assumptions of Rationality This handbook will be of interest to those wanting a broad spectrum and overview of late 20th - early 21st century sociological theory.